ANALYSIS OF COMPETITIVE ADVANTAGE IN AN EFFORT TO IMPROVE PRODUCT CREATIVITY AND PRODUCT INNOVATION FOR HONDA MOTORCYCLES - Rahmi Rahmi; Nelly Nelly; Fanny Nailufar; Zuriani Ritonga; Hayanuddin Safri (SEAN Institute, 2022)
This study aims to determine the effect of product creativity and product innovation on competitive advantage on Honda motorcycles in Banda Aceh City. The population in this study were 100 consumers of Honda motorcycles in Banda Aceh City, with a total sample of 100 respondents using a convenience sampling technique. The model used in this study is multiple linear regression analysis. The results of the research show that product creativity and product innovation simultaneously and partially significant effecttocompetitive advantage on Honda brand motorbikes in Banda Aceh City. Score correlation coefficient (R) of 0.653 indicates that the relationship (correlation) between the independent variables and the dependent variable is 0.653 or 65.3%, meaning. Competitive advantage of Honda motorcycles in Banda Aceh City has a moderate relationship with product creativity (X1) and product innovation (X2). While the coefficient of determination (R2) is 0.427, meaning that any changes in the competitive advantage variable can be explained by the product creativity variable (X1) and product innovation (X2) of 0.427 or 42.7% and the remaining 57.3% is explained by the variable other outside of this research for example product quality, service quality, trust, corporate image and others.